Come home eaudiobook A novel. - Scottoline, Lisa (Macmillan Audio, 2012)
Lisa Scottoline has delivered taut thrillers with a powerful emotional wallop in her New York Times bestsellers Save Me, Think Twice, and Look Again . Now, with her new novel, Come Home, she ratchets up the suspense with the riveting story of a mother who sacrifices her future for a child from her past. Jill Farrow is a typical suburban mom who has finally gotten her and her daughter's lives back on track after a divorce. She is about to remarry, her job as a pediatrician fulfills her—-though it is stressful—-and her daughter, Megan, is a happily over-scheduled thirteen-year-old juggling homework and the swim team. But Jill's life is turned upside down when her ex-stepdaughter, Abby, shows up on her doorstep late one night and delivers shocking news: Jill's ex-husband is dead. Abby insists that he was murdered and pleads with Jill to help find his killer. Jill reluctantly agrees to make a few inquiries and discovers that things don't add up. As she digs deeper, her actions threaten to rip apart her new family, destroy their hard-earned happiness, and even endanger her own life. Yet Jill can't turn her back on a child she loves and once called her own. Come Home reads with the breakneck pacing of a thriller while also exploring the definition of motherhood, asking the questions: Do you ever stop being a mother? Can you ever have an ex-child? What are the limits to love of family?